2016
DOI: 10.1038/ncomms11373
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical cell competition kills cells via induction of lethal p53 levels

Abstract: Cell competition is a quality control mechanism that eliminates unfit cells. How cells compete is poorly understood, but it is generally accepted that molecular exchange between cells signals elimination of unfit cells. Here we report an orthogonal mechanism of cell competition, whereby cells compete through mechanical insults. We show that MDCK cells silenced for the polarity gene scribble (scribKD) are hypersensitive to compaction, that interaction with wild-type cells causes their compaction and that crowdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
260
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(276 citation statements)
references
References 70 publications
15
260
1
Order By: Relevance
“…This model may apply to several mutations that promote growth/proliferation and inhibit apoptosis (e.g., Hippo pathway, Ras, EGF). A similar process was recently involved in the elimination of Scribble mutant MDCK cells surrounded by WT cells [67]. The higher levels of p53 in Scribble mutant cells increase their sensitivity to compaction, which is sensed through the activation of p53 by Rho-associated kinase (ROCK) and the stress kinase p38.…”
Section: ([ 5 _ T D $ D I F F ] Figures 1c And[ 1 _ T D $ D I F F ]mentioning
confidence: 72%
“…This model may apply to several mutations that promote growth/proliferation and inhibit apoptosis (e.g., Hippo pathway, Ras, EGF). A similar process was recently involved in the elimination of Scribble mutant MDCK cells surrounded by WT cells [67]. The higher levels of p53 in Scribble mutant cells increase their sensitivity to compaction, which is sensed through the activation of p53 by Rho-associated kinase (ROCK) and the stress kinase p38.…”
Section: ([ 5 _ T D $ D I F F ] Figures 1c And[ 1 _ T D $ D I F F ]mentioning
confidence: 72%
“…The activation of myosin-II generates pulling-forces exerted at the interface between normal and transformed cells, thereby promoting apical extrusion of the transformed cells (6). Along the same line, recent studies have revealed that physical forces or mechanical tensions can play a crucial role in cell competition between normal and transformed epithelial cells (32,33). Thus, the EPLIN-myosin-II pathway could be another endocytosismediated regulatory mechanism for apical extrusion.…”
Section: Discussionmentioning
confidence: 98%
“…They also used Mdm2 +/− hematopoietic stem and progenitor cells to genetically mimic mild p53 activation induced by a low level of irradiation and found that these cells were outcompeted by the wild-type donor in the chimeric hematopoietic system (29). More recently, it was shown that p53 may instruct an out-competition phenotype of the scrib KD cells in response to cell crowding (30). However, it remains elusive whether cell competition represents a general mechanism in p53-mediated cellular responses or occurs only under specific circumstances.…”
Section: Mdm4mentioning
confidence: 99%